Fuel scarcity or household wealth? Assessing the drivers of cooking energy consumption patterns in rural areas in East Africa. Issue 1 (2nd January 2023) - Matavel, Custodio Efraim; Hoffmann, Harry; Hafner, Johannes Michael; Kipkulei, Harison Kiplagat; Uckert, Götz; Kaingo, Jacob; Salavessa, João; Mbwana, Hadijah A.; Issa, Ramula; Novela, Leonel Silva; Sieber, Stefan; Rybak, Constance
ABSTRACT: Rural households in Tanzania and Mozambique depend mainly on charcoal, firewood and other traditional fuels, such as cow dung or agriculture by-products, to cook. Simultaneously, fuel scarcity is an important phenomenon that leads households to apply coping strategies such as reducing the number of meals or increasing walking distance to collect firewood. Despite the well-known negative health, economic and potential ecologic impacts, the transition away from solid biomass energy sources is not expected in the short run. Thus, understanding the patterns of biomass energy consumption is essential to allow sustainable development in the household cooking sector. In this study, we evaluated the influence of wealth status and fuelwood scarcity on household energy choices in four villages with case study sites in Mozambique and Tanzania. The fuel usage patterns are consistent with the 'energy stacking' model as, despite an increase in the consumption of charcoal, firewood remains the principal cooking fuel. Wealth does not necessarily result in a transition toward cleaner fuels, nor does scarcity result in the use of other forms of traditional bioenergy. We suggest the promotion of fuel reduction strategies such as improved cookstoves or the implementation of on-farm trees to reduce the pressure on forests.